A Study to Evaluate the Effectiveness of a Structured Teaching Program on Knowledge Regarding Academic Procrastination and its Management Using Cognitive Behavioral Therapy Techniques Among Higher Secondary School Teachers in a Selected School - Sharmila, J. (Journal of Neonatal Surgery, 2025)
Academic procrastination is a frequent issue among students, often under-recognized or ineffectively addressed by teachers. This study evaluates the effectiveness of a structured teaching program (STP) in enhancing teachers’ knowledge of academic procrastination and its management using cognitive behavioural therapy (CBT) techniques. A quantitative evaluative design with pre-test and post-test was conducted among 50 higher secondary school teachers. The findings reveal significant improvement in knowledge post-intervention, affirming the utility of CBT-based STP in teacher education